L p Estimates for Weak Solutions to Nonlinear Degenerate Parabolic Systems - Wei, N.; Ge, X.; Wu, Yong Hong; Zhao, L. (Hindawi Publishing Coporation, 2017)
This paper is devoted to the Lp estimates for weak solutions to nonlinear degenerate parabolic systems related to Hörmander's vector fields. The reverse Hölder inequalities for degenerate parabolic system under the controllable growth conditions and natural growth conditions are established, respectively, and an important multiplicative inequality is proved; finally, we obtain the Lp estimates for the weak solutions by combining the results of Gianazza and the Caccioppoli inequality.